tarigor
?>

Упрости выражение -2с^3(3+16c^2) - (c^2 + 4) * 3c^3 + 6(3c^3+1)

Алгебра

Ответы

det-skazka55

-35c⁵+6

Объяснение:

-2с^3(3+16c^2) - (c^2 + 4) * 3c^3 + 6(3c^3+1) =

= -6c³-32c⁵-(3c⁵+12c³)+18c³+6 =

= -6c³-32c⁵- 3c⁵ - 12c³+18c³+6 =

= -35c⁵+6

Ответить на вопрос

Поделитесь своими знаниями, ответьте на вопрос:

Упрости выражение -2с^3(3+16c^2) - (c^2 + 4) * 3c^3 + 6(3c^3+1)
Ваше имя (никнейм)*
Email*
Комментарий*

Популярные вопросы в разделе

satinvova
Mariya-Karaseva
Test Станислав
Log(1/2)(x^2+x)+1>=0решите
abuley
tomogradandrey
kgrechin
Александрович175
AkulovaAnastasiya
alfaduk24908
komolovda
Novikova Aleksandrovna
kolyabelousow4059
sveta740450
platonovkosty
schernov